2018
DOI: 10.21577/0100-4042.20170247
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nanoemulsion Containing a Natural Naphthoquinone

Abstract: publicado na web em 07/06/2018 Natural naphthoquinones such as lapachol (Lp) have demonstrated promising biological activities. However, these quinones present low systemic biodisponibility due to its poor aqueous solubility. To overcome this problem, nanoemulsions (NE) formed by oily core are able to incorporate hydrophobic molecules thus enabling them to be dispersed into an aqueous phase. The present study reports the development, characterization, and physical stability of NE containing lapachol. NE formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…The in vitro release experiments of the EO were carried out using the dialysis technique ( Rodrigues et al., 2018 ). An aliquot of nanoemulsion was placed inside a dialysis bag (cellulose membrane, molecular weight cut-off 14,000 Da, Roth®), sealed, and immersed in a vessel containing 150 mL of 10 mM phosphate buffer solution (PBS, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro release experiments of the EO were carried out using the dialysis technique ( Rodrigues et al., 2018 ). An aliquot of nanoemulsion was placed inside a dialysis bag (cellulose membrane, molecular weight cut-off 14,000 Da, Roth®), sealed, and immersed in a vessel containing 150 mL of 10 mM phosphate buffer solution (PBS, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…The use of a surfactant is believed to alter the electrostatic charge in the nanoemulsion which causes low aggregation [19]. The influence of single and complex surfactants in nanoemulsion formation has been studied previously [20]. Some studies have demonstrated mixed surfactant is capable to produce better hydrophilic-lipophilic balance (HLB), enhances the flexibility of the surfactant layer and ability to partition at high levels into the oil-water interface.…”
Section: Surfactant As An Emulsifier In Nanoemulsionmentioning
confidence: 99%
“…The samples were stored at 25 °C for 195 days and then their stability was evaluated based on the particle size (D H ), particle size distribution and zeta potential. The literature data indicate that sufficiently high and sufficiently low potential zeta values (up to 30mV and below −30mV, respectively) enhance the stability and functionality [ 37 , 38 , 39 ]. Unfortunately, the storage period had a destructive effect on the systems with solubilized curcumin in CA—flocculation was observed, while systems with Vit C and Vit E remained clear, with slight opacity.…”
Section: Resultsmentioning
confidence: 99%